Takayasu arteritis: a review. Issue 7 (1st July 2002) - Johnston, S L; Lock, R J; Gompels, M M
Abstract : Takayasu arteritis is a well known yet rare form of large vessel vasculitis. This review details the history, clinical features, differential diagnoses, classification, and immunology of the disorder. Suppression of inflammation and preservation of vascular competence are the aims of treatment. As with any rare disease, randomised controlled treatment trials are either lacking or based on small patient numbers, making management decisions difficult. Current evidence based treatments are presented and discussed.